Sistem Pendukung Keputusan Seleksi Beasiswa Menggunakan Metode Topsis Berbasis WEB (Studi Kasus Beasiswa Bank Indonesia) - Muhamad Sadali; Muhammad Wasil; Indra Gunawan; Ahmad Fariza (Infotek: Jurnal Informatika dan Teknologi, 2023)
Basically, the decision support system is a computer-based system that helps in the decision-making process. A Decision Support System is a computer system that processes data into information to make decisions from specific semi-structured problems that were specifically developed to support solutions to unstructured management problems to improve the quality of decision-making. This support system helps in the decision-making process in selecting the internal administration of Bank Indonesia scholarships at Hamzanwadi University. In this decision support system, criteria are needed to determine who will be selected to receive the scholarship. In this study, the author uses the TOPSIS (Technique for Order Preference by Similarity to Ideal Solution) method as a decision-making method. The TOPSIS method was chosen because it is used to find alternatives with certain criteria. The method used in the preparation and design of the application to be built is to use the Software Development Life Cycle (SDLC) method with a design using the Unified Modeling Language (UML) with object-oriented programming concepts. The system that has been made is said to be suitable for use because the results of the recommendations are in accordance with user expectations and the scholarship selection process becomes more effective and efficient.